Part A: Investigation of a newly identified plant Hernandia didymantha Donn, synthesis of phenethyl cinnamide Part B: Selective removal of ascaridol from the essential oil of Chenopodium ambrosioides var ambrosioides Part C: Synthesis of canophyllol analogues - Primeau, Lynn (University of Ottawa (Canada), 2007)
Part A. A number of constituents isolated from the ethanol extracts of the leaves of the neotropical species Hernandia Didymantha Donn. These include series of ethyl esters of common C14, C16, and C18 saturated and unsaturated fatty acides. The presence of the ethyl ester of the CI7 fatty acid was indicated by GC-MS. The major non polar component was shown to be nerolidol, 4, an open chain sesquiterpene. Ethnobotanical reports indicate that this sesquiterpene can be used as a natural pesticide and as a transdermal carrier. It is also reported to have anti-malarial activity. The major more polar component was shown to be the tryptamine derivative phenethyl cinnamide, 1. The structure identification was based on comparison of literature data and a two step synthesis (80%) from cinnamic acid and tryptamine. Part B. Chenopodium ambrosioides has been known for centuries as an antifungal and vermifuge remedie. As an infusion, Chenopodium ambrosioides is safe and an effective treatment. The essential oil has been investigated as an organic insecticide by Codena Inc, (St Charles sur Richelieu, Quebec). Registration was initially rejected by the U.S. Environmental Protection Agency because of the known toxicity of one of the components, the monoterpene endoperoxide ascaridol, compound 26. The selective removal of ascaridol was achieved without affecting the other constituents present in the essential oil using either the reaction with zinc in acetic acid or Lindlar Catalyst poisoned with quinoline and hydrogen at room temperature under several atmospheres of pressure. In each case the reduction product is the diol 27. The treated oil still showed excellent insecticidal properties and was approved for use as an organic pesticide by the U.S. Environmental Protection Agency. Considerable efforts were made to optimize the zinc/acetic acid. Unfortunately the optimized procedure still required considerable excess amounts of both reagents. This procedure, although successful from a chemistry and safety point of view, was not economically viable. The second method using the poisoned Lindlar Catalyst and H2 a gave clean reduction of ascaridol without causing reduction of any of the many olefinic components present in the oil. We showed that the catalyst could be recycled at least five times without significant loss of activity. Finally to give a reduced essential oil free of any quinoline, we prepared catalyst in hexane and removed the excess quinoline by washing several times with hexanes. Metallic contaminants in the oil such as lead and palladium which are components of the Lindlar catalyst were effectively removed by stirring the final product with 1% silica gel followed by filtration. This method appears to be inexpensive and thus suitable for commercial production of the safe "Codena Oil". Part C. Literature reports have shown that ursolic acid, a triterpene acid has a positive effect on the elimination of biofilms without any damage to the bacteria function. Since ursolic acid and canophyllol are both pentacyclic triterpenes a series of analogues of canophyllol have been synthesized and characterized by 1H NMR, 13C NMR, MS and their melting points. These compounds in which we made relatively simple changes in the functionality at C-3 and C-28 of the canophyllol molecule, together with a variety of similar betulinic acid compounds are now available for testing as potential controls of biofilm formation. These test will be carried out by the research group of Dr. R. Sattar of the University of Ottawa, Faculty of Medicine. Canophyllol was obtained as the major triterpene component in the bark of Ruptilliocarpon caracolito collected in the Osa Penninsula, Costa Rica.
Keywords: Chemistry, Organic.